2015
DOI: 10.1002/smll.201403422
|View full text |Cite
|
Sign up to set email alerts
|

Surface Plasmon‐Enhanced Photodetection in Few Layer MoS2 Phototransistors with Au Nanostructure Arrays

Abstract: 2D Molybdenum disulfide (MoS2 ) is a promising candidate material for high-speed and flexible optoelectronic devices, but only with low photoresponsivity. Here, a large enhancement of photocurrent response is obtained by coupling few-layer MoS2 with Au plasmonic nanostructure arrays. Au nanoparticles or nanoplates placed onto few-layer MoS2 surface can enhance the local optical field in the MoS2 layer, due to the localized surface plasmon (LSP) resonance. After depositing 4 nm thick Au nanoparticles sparsely o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
243
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 373 publications
(253 citation statements)
references
References 46 publications
7
243
0
1
Order By: Relevance
“…Several strategies have been proposed and preliminary demonstrations have been reported including use of plasmonic metal particles, shells or resonators to enhance photocurrent and photoluminescence. [27][28][29][30][31][32][33][34][35][36][37] More sophisticated and lossless dielectric optical cavities such as photonic crystals and ring resonators have also been used to enhance absorption, mainly aimed at emission applications in monolayer samples. [38][39][40][41] For large area photovoltaic applications, light trapping strategies that involve little or no micro-or nanofabrication and patterning are desirable to improve performance while minimizing cost.…”
Section: Absorption and Photonic Designmentioning
confidence: 99%
“…Several strategies have been proposed and preliminary demonstrations have been reported including use of plasmonic metal particles, shells or resonators to enhance photocurrent and photoluminescence. [27][28][29][30][31][32][33][34][35][36][37] More sophisticated and lossless dielectric optical cavities such as photonic crystals and ring resonators have also been used to enhance absorption, mainly aimed at emission applications in monolayer samples. [38][39][40][41] For large area photovoltaic applications, light trapping strategies that involve little or no micro-or nanofabrication and patterning are desirable to improve performance while minimizing cost.…”
Section: Absorption and Photonic Designmentioning
confidence: 99%
“…First, the introduction of photonic structures into 2D materials can significantly enhance their photoresponsivity [93][94][95][96][97][98][99][100][101][102][103][104][105][106]. On the other hand, by electrostatically tuning the Fermi level of 2D materials, with which photonic structures like waveguides, resonators and cavities are integrated, their modulation performance can be improved [107][108][109][110][111][112][113].…”
Section: Photonic Structure-integrated 2d Materials Optoelectronicsmentioning
confidence: 99%
“…Similar phenomena are observed for 2D material base optoelectronics. A large enhancement of photocurrent response can be obtained by coupling few-layer MoS 2 with Au plasmonic nanostructure arrays [99]. Depositing 4 nm thick Au nanoparticles sparsely onto few-layer MoS 2 phototransistors leads to a two-fold increase in the photocurrent response.…”
Section: Photodetectormentioning
confidence: 99%
“…Moreover, Hu's group observed that a large enhancement of photocurrent response is obtained by decorating multi-layer MoS 2 with plasmonic gold nanoparticles array. Due to LSPR, the photocurrent of MoS 2 phototransistors exhibited a threefold enhancement after depositing periodic Au nanoparticles arrays [19].…”
mentioning
confidence: 99%